Mid-trimester amniotic fluid proteome's association with spontaneous preterm delivery and gestational duration - Hallingstrom, Maria; Zedníková, Petra; Tambor, Vojtech; Barman, Malin; Vajrychova, Marie; Lenco, Juraj; Viklund, Felicia; Tancred, Linda; Rabe, Hardis; Jonsson, Daniel; Kachikis, Alisa; Nilsson, Staffan; et al. (Public Library of Science, 2020)
Background Amniotic fluid is clinically accessible via amniocentesis and its protein composition may correspond to birth timing. Early changes in the amniotic fluid proteome could therefore be associated with the subsequent development of spontaneous preterm delivery. Objective The main objective of this study was to perform unbiased proteomics analysis of the association between mid-trimester amniotic fluid proteome and spontaneous preterm delivery and gestational duration, respectively. A secondary objective was to validate and replicate the findings by enzyme-linked immunosorbent assay using a second independent cohort. Methods Women undergoing a mid-trimester genetic amniocentesis at Sahlgrenska University Hospital/Ostra between September 2008 and September 2011 were enrolled in this study, designed in three analytical stages; 1) an unbiased proteomic discovery phase using LC-MS analysis of 22 women with subsequent spontaneous preterm delivery (cases) and 37 women who delivered at term (controls), 2) a validation phase of proteins of interest identified in stage 1, and 3) a replication phase of the proteins that passed validation using a second independent cohort consisting of 20 cases and 40 matched controls. Results Nine proteins were nominally significantly associated with both spontaneous preterm delivery and gestational duration, after adjustment for gestational age at sampling, but none of the proteins were significant after correction for multiple testing. Several of these proteins have previously been described as being associated with spontaneous PTD etiology and six of them were thus validated using enzyme linked immunosorbent assay. Two of the proteins passed validation; Neutrophil gelatinase-associated lipocalin and plasminogen activator inhibitor 1, but the results could not be replicated in a second cohort. Conclusions Neutrophil gelatinase-associated lipocalin and Plasminogen activator inhibitor 1 are potential biomarkers of spontaneous preterm delivery and gestational duration but the findings could not be replicated. The negative findings are supported by the fact that none of the nine proteins from the exploratory phase were significant after correction for multiple testing.
Spojení proteomu amniotické tekutiny v polovině trimestru se spontánním předčasným porodem a délkou těhotenství
Keywords: gelatinase-associated lipocalin; biomarker discovery; microbial invasion; premature rupture; multiple proteins; labor; inflammation; prediction; infection; women; lipocalin asociovaný s želatinázou; objev biomarkerů; mikrobiální invaze; předčasné prasknutí; více proteinů; práce; zánět; předpověď; infekce; ženy